The Development of Instructional Packages on Virtue Morality and Teacher Code of Conduct using the Cooperative Learning Technique for Students with a Graduate Diploma Students in Teaching Profession Ubon Ratchathani Rajabhat University - Pratumvian, Chucheep (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Collaborative learning is an approach to learning that prioritizes the learners themselves because it offers a variety of teaching formats tailored to the learning objectives. Learners collaborate and assist each other in the learning process. This research aimed (1) to develop teaching packages in Virtue Morality and Teacher Code of Conduct using the Cooperative learning technique criteria at 80/80 (2) to study the effectiveness index of the teaching package before and after using the packages, (3) to study the satisfaction of the packages. Methodology: The research methodology is quantitative research. The target audience was 60 students majoring in a graduate diploma (teaching profession) in the first-semester academic year 2023 using a purposive sampling method. The teaching packages were implemented in the first semester of the academic year 2023. The researcher used three packages. The instruments in the research were six units of the teaching packages, the achievement test, and the questionnaire. The index of discrimination and reliability was .852. The data were analyzed by arithmetic mean, standard deviation, percentage, and effectiveness index (E.I). Results: (1) The developed packages were efficient as they exceeded the standard criteria of 81.21/84.48. (2) The effectiveness index (E.I) of the student's achievement after using the package set is equal to 0.7242, indicating that students have progressively increased learning by 72.42 (3) The packages were rated by the students at a high level as a whole, by domain, and by item. Conclusion: Collaborative learning is a method of managing learning where students collaborate and assist each other in learning by dividing them into small groups with varying abilities. This grouping is characterized by clear and structured teamwork. There is collaborative work, exchange of ideas, mutual support and reliance, and shared responsibility both individually and collectively.